Protein and gluten content in grain of the winter bread wheat varieties, depending on the forecrop - O. A. Nekrasova; N. S. Kravchenko; N. G. Ignatieva; O. V. Skripka; S. N. Gromova (Зерновое хозяйство России)
One of the important tasks facing agriculture is to increase the production of high quality grain. It is known knowledge that the variety is a dynamic biological factor capable of realizing its genetic potential with a different combination of environmental factors and can act as a biological foundation for the production of high quality grain. The forecrop in modern agriculture acts as an independent factor in increasing grain yield and quality. The purpose of the current study was to estimate protein and gluten content in grain of winter bread wheat varieties of intensive type when sown after maize for grain and sunflower in the conditions of the Rostov region. The objects of the study were 9 winter bread wheat varieties of the intensive type developed in the FSBSI “ARC “Donskoy”. The study was carried out in the fields of the department of winter wheat breeding and seed production in 2018–2020. There were identified the varieties that formed the largest percentage of protein in grain on average over the years of study. They were the varieties ‘Etyud’, ‘Yubiley Dona’ and ‘Shef’ (12.44–13.06%) sown after maize for grain, and the varieties ‘Rubin Dona’, ‘Shef’ and ‘Zodiak’ (14.09–14.33%) sown after sunflower. There have been identified the varieties ‘Zodiak’ and ‘Yubiley Dona’ with the largest amount of gluten in grain on average over the years of study. They produced 24.63%, 25.53%, respectively after maize for grain; after sunflower they produced 28.20%, 27.66%, respectively. The results of two-way analysis of variance proved a greater effect of the factor ‘forecrop’ on protein and gluten content in grain of winter bread wheat than the effect of the factor ‘variety’ and their correlation.